STRUKTUR KOMUNITAS MANGROVEDI KABUPATEN MUNA - Rahman, Rahman; Yanuarita, Dewi; Nurdin, Nardiati (Torani Journal of Fisheries and Marine Science, 2014)
Mangrove ecosystem in Muna Regency,includingKembarMaminasa village, has been started to be exploited bythe local community. Unfortunately information about mangrove status and their condition are still negligible.The result of this study is useful to provide basic information for sustainable management of mangroveecosystems. A study of mangrove community structure was conducted at the Tembe River inKembar Maminasavillage, from September to November 2013. Mangrove community structure was analyzed using non-metricmultidimensional scaling technique and Bray-Curtis cluster analysis, while the most contributed species todifference of fish community structure was analyzed using SIMPER (similarity of percentages) procedure. Thedifference between the community structure in three different substrates(muddy, mud-sandy, sand-muddy) wasanalyzed using ANOSIM. All the statistics analysis were carried out using PRIMER v6 software.The results ofthe study showed that there were seven species found in the Desa Kembar Maminasa and they tended todistribute differently among three different substrate, creating three slightly different zones of mangrove fromseaward to landward. The community structure of the mangrove trees were different among the three differentsubstrates. Similar results were found in community structure of mangrove saplings and mangrove seedlings. Key words: District Muna, community structure of mangrove, mangrove tree, mangrove saplings, mangroveseedlings.